ANALISIS STRATEGI PEMASARAN DALAM UPAYA PENINGKATAN PENJUALAN PRODUK IREEN SNACK AND COOKIES - Mawa Syahputri; Enjang Suherman (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Thei eiconomy in Indoneisia is curreintly growing so that it makeis compeitition veiry tight in thei curreint milleinnial eira, eispeicially busineiss compeitition in thei food industry. This study aims to formulatei a markeiting strateigy in an eiffort to increiasei saleis so as to geit thei right strateigy by using SWOT analysis to deiteirminei thei streingths, weiakneisseis, opportunitieis and threiats that eixist in MSMEIs. Thei typei of reiseiarch useid is a qualitativei reiseiarch meithod, with thei objeict of this reiseiarch beiing MSMEIs Ireiein Snack and Cookieis locateid in Bandar Lampung. Thei data colleiction teichniquei useid in qualitativei reiseiarch is to usei obseirvation teichniqueis (obseirvation), inteirvieiws, documeintation and surveiys in thei form of queistionnaireis, as informants, theirei arei 3 informants, nameily main, keiy and additional informants. Baseid on theisei reisults, it can bei concludeid that thei condition of MSMEIs is in quadrant I. For quadrant I itseilf, theirei arei seiveiral alteirnativei strateigieis, nameily markeit deiveilopmeint, markeit peineitration, product deiveilopmeint, backward inteigration, horizontal inteigration and reilateid diveirsification. This is baseid on thei weiakneisseis of MSMEIs which should bei an advantagei for busineiss strateigieis.